2022
DOI: 10.1111/tid.13814
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sexually transmitted infections is lower among kidney transplant recipients compared to the general population—A nationwide cohort study

Abstract: Aim:The burden of sexually transmitted infections (STI) among solid-organ transplant recipients is currently unknown. We studied the risk of STIs among kidney transplant recipients compared with the general population in a nationwide cohort. Methods: Between 2002 and 2019, all microbiological findings of Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum (syphilis), and human immunodeficiency virus among kidney transplant recipients <65 years and transplanted between 1995 and 2017 in our country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…By chance, 1 recipient was infected after receiving a kidney from his spouse with active syphilis infection even when prophylactic measures were implemented. In the nationwide cohort study evaluating the burden of sexually transmitted infections after transplantation, 25 of 3,612 recipients were confirmed to have acquired infections, including 1 case of syphilis ( 14 ). Those findings underscore the imperative for recipients and their spouses to undergo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By chance, 1 recipient was infected after receiving a kidney from his spouse with active syphilis infection even when prophylactic measures were implemented. In the nationwide cohort study evaluating the burden of sexually transmitted infections after transplantation, 25 of 3,612 recipients were confirmed to have acquired infections, including 1 case of syphilis ( 14 ). Those findings underscore the imperative for recipients and their spouses to undergo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 A small cross-sectional review of 49 adolescent renal transplant recipients found a 30% STI prevalence in targeted screening of symptomatic patients compared to 15% prevalence in the general adolescent clinic population offering universal screening. 40 In the review of a large database of SOT recipients, the highest frequency of STI was seen among patients transplanted during adolescence, 41 suggesting that screening and counseling efforts should be focused on AYA. STIs can be severe and difficult to eradicate in immune-suppressed patients.…”
Section: S E Xually Tr An S Mit Ted Infec Tionsmentioning
confidence: 99%